2019
DOI: 10.1029/2019jb018178
|View full text |Cite
|
Sign up to set email alerts
|

How Accurately Can We Model Magma Reservoir Failure With Uncertainties in Host Rock Rheology?

Abstract: Forecasting the onset of a volcanic eruption from a closed system requires understanding its stress state and failure potential, which can be investigated through numerical modeling. However, the lack of constraints on model parameters, especially rheology, may substantially impair the accuracy of failure forecasts. Therefore, it is essential to know whether large variations and uncertainties in rock properties will preclude the ability of models to predict reservoir failure. A series of two‐dimensional, axisy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…Approximately half of all deformation events are intrusive (i.e., not immediately followed by an eruption (Biggs et al, ). Numerical models suggest that frequency of eruption is dependent on timescale of injection (Degruyter & Huber, ; Zhan & Gregg, ), particularly in smaller reservoirs (Gregg et al, ). However, it is unclear whether intrusive events are generally observed to have lower deformation rates than do episodes of intrusion that lead to eruption or if there is a threshold deformation rate for intrusion vs eruption.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of all deformation events are intrusive (i.e., not immediately followed by an eruption (Biggs et al, ). Numerical models suggest that frequency of eruption is dependent on timescale of injection (Degruyter & Huber, ; Zhan & Gregg, ), particularly in smaller reservoirs (Gregg et al, ). However, it is unclear whether intrusive events are generally observed to have lower deformation rates than do episodes of intrusion that lead to eruption or if there is a threshold deformation rate for intrusion vs eruption.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the structure of Young's modulus used in the models will also affect the failure forecasts. If we underestimate the Young's modulus, the real overpressure to create the same surface deformation will be higher than the model prediction (Zhan & Gregg, ). Our model predicts higher Vp and Vs than the regional velocity models above 5 km (Figure S1), which rules out the possibility of a significant underestimation of the Young's modulus.…”
Section: Failure Of the Host Rock Without Pore Fluidmentioning
confidence: 90%
“…Similar to Zhan and Gregg (2019), host-rock failure initiates as the overpressure of the magma reservoir is increased. The occurrence of Coulomb failure or tensile failure can be predicted by τ>C 0 cosϕ i þ σ n sinϕ i ;…”
Section: Failure Criterionmentioning
confidence: 98%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ presented in the supplementary materials. For further discussion of the impact of elastic and viscoelastic properties on results of unrest models we refer the reader to Zhan et al 16 and Head et al 31 , respectively.…”
Section: Model Sensitivity To Rheologymentioning
confidence: 99%
“…Low-pressure, high-temperature deformation experiments reveal that Young's modulus in particular is highly temperature dependent at brittle-ductile transition temperatures of 600-750 °C 12 . Furthermore, thermomechanical models of volcano deformation have shown that Young's modulus greatly affects predicted surface deformation and strain accumulation [13][14][15] , and a recent investigation showed that rheology strongly impacts failure potential 16 .…”
mentioning
confidence: 99%